1992
DOI: 10.1002/bit.260400704
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mass transfer limitations on determination of the half saturation constant for hydrogen uptake in a mixed‐culture CH4‐producing enrichment

Abstract: There is strong evidence in the literature supporting the existence of significant mass transfer limitations on the kinetics of exogenous H(2) consumption by methanogens. The half saturation constant for H (2) uptake by a mixed-culture, CH(4) producing enrichment was measured using an experimental protocol that avoided internal mass transfer limitations. The value obtained was two orders of magnitude smaller than any other previously reported. A mathematical model for acetogenic syntrophic associations was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Thus, substrate threshold values appear to be a new and important parameter that may significantly influence anaerobic reactions such as hydrogen oxidation. The use of the H2 threshold value in kinetic models has also been proposed recently (Giraldo-Gomez et al, 1992). When the concentration of the substrates is far higher than that of the products and the reaction driving force is large, the ratio T/K becomes very small and the model predictions approach those of the classical Michaelis-Menten model (see also Figs.…”
Section: General Model Behaviormentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, substrate threshold values appear to be a new and important parameter that may significantly influence anaerobic reactions such as hydrogen oxidation. The use of the H2 threshold value in kinetic models has also been proposed recently (Giraldo-Gomez et al, 1992). When the concentration of the substrates is far higher than that of the products and the reaction driving force is large, the ratio T/K becomes very small and the model predictions approach those of the classical Michaelis-Menten model (see also Figs.…”
Section: General Model Behaviormentioning
confidence: 97%
“…These threshold values indicated that bacterial reaction kinetics do not necessarily result in the complete utilization of the substrate. The existence of hydrogen threshold values indicated that v,,, values and k , values alone may not be sufficient to predict the efficiency of utilization of low hydrogen concentrations (Giraldo-Gomez et al, 1992;Lovley, 1985). These hydrogen threshold values were found to be related to the free energy change of the reaction (Cord-Ruwisch et al, 1988).…”
Section: General Model Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“… 1, Vroblesky and colleagues (1997); 2, Christensen and colleagues (2000); 3, Lovley and colleagues (1982); 4, Conrad and colleagues (1985); 5, Lovley and Goodwin (1988); 6, Hoehler and colleagues (1998); 7, Jakobsen and colleagues (1998); 8, Hoehler and colleagues (2002); 9, Roden and Wetzel (2003); 10, Kaspar and Wuhrmann (1978); 11, Fukuzaki and colleagues (1990); 12, Warikoo and colleagues (1996); 13, Hoh and Cord‐Ruwisch (1997); 14, Fennell and Gossett (1998); 15, Kristjansson and colleagues (1982); 16, Robinson and Tiedje (1984); 17, Dwyer and colleagues (1988); 18, Westermann and colleagues (1989); 19, Giraldo‐Gomez and colleagues (1992); 20, Schmidt and Ahring (1993); 21, Smatlak and colleagues (1996); 22, Ballapragada and colleagues (1997); 23, Voolapalli and Stuckey (1999); 24, van Bodegom and Scholten (2001); 25, Oude Elferink and colleagues (1998); 26, Scholten and colleagues (2002); 27, Ahring and Westermann (1988); 28, Boone and colleagues (1989); 29, Kleerebezem and Stams (2000); 30, Dolfing and Tiedje (1988); 31, Beaty and McInerney (1989). …”
Section: Resultsmentioning
confidence: 99%
“…The biological part of the model is described by the biomass production dependencies. In the literature (e.g., Angelidaki et al, 1993;Buffiere et al, 1995;Giraldo-Gomez et al, 1992) there is evidence to suggest that Monod-type kinetics would be sufficient to portray acidogenic growth on glucose, growth of the syntrophic association on hydrogen, and methanogenic growth on acetate,…”
Section: Model Developmentmentioning
confidence: 97%